Optimal biorefinery design and supply chain for the production of sugarcane bagasse pellets, electricity and bioethanol in Colombia - Infante Cuan, Jorge Eduardo; Fernandes Garcia, Victor; Viana Ensinas , Adriano (International Journal of Sustainable Energy Planning and Management, 2025)
Biofuels are considered an alternative to sustainable energy production due to their potential to reduce greenhouse gas emissions. This paper presents a mixed integer linear programming (MILP) model to evaluate the optimal configuration of a supply chain for the production of bioethanol, electricity and bagasse pellets from sugarcane potential in Colombia. The results show that gasoline demand in Colombia is met through bioethanol production, and the demand for coal used in thermoelectric plants can be met through the production of bagasse pellets from 17 biorefineries located in 13 study regions. The avoided emissions represent 25.17% of the target proposed by the Colombian government, and transport emissions represent only 2.62% of the emissions generated by the model. Despite the promising results obtained in the optimization of the supply chain for bioethanol and bagasse pellet production in Colombia, there are challenges and limitations that must be considered. One of the main challenges lies in the uncertainty associated with the variability in biomass, bioethanol, and carbon credit prices, which can affect the long-term economic viability of the project. The sustainability of land use for sugarcane production must be assessed with a more detailed approach to avoid conflicts with food production and ecosystem conservation. These aspects represent key opportunities for future research and improvements in strategic planning for the bioenergy sector. Finally, the sensitivity analysis shows that the ±20% variation in the price of sugarcane and the price of bioethanol have a high impact on the payback period with respect to the base case.